POWER SYSTEM PLANNING AND OPERATION - Simon, Sishaj Pulikottil; Padhy, Narayana Prasad; Park, Jong-Bae; Lee, Kwang Y.; Zhou, Ming; Xia, Shu; da Silva, Anna Carolina R.H.; Choi, Jaeseok; Lee, Yeonchan; Lambert-Torres, Germano; Salomon, Camila Paes; da Silva, Luiz Eduardo Borges; et al. (Wiley, 2020)
This chapter provides implementation of various optimization algorithms to various power system problems that utilize power flow calculations. Determination of the schedule (ON/OFF status and amount of power generated) of generating units within a power system results in great saving for electric utilities. The unit commitment problem can be formulated in order to minimize the total operating cost, satisfying the system, the unit, and several operational constraints. The power transfer limit of overhead transmission lines (OTLs) is an important constraint for power systems’ planning and operation. This constraint plays an essential role in the secure and economic management of power systems. The chapter presents economic dispatch problem by considering GAs and particle swarm optimization (PSO) in complex power system analysis. It uses a hybrid PSO to solve load flow problem while uses artificial bee colony optimization for solving the optimal power flow problem.
Keywords: Artificial bee colony optimization; Classical constructive heuristic algorithms; Optimal power flow problem; Particle swarm optimization; Power system planning; Unit commitment problem